Sperm quality and optimal size of mature male giant tiger prawn (Penaeus monodon fabricius) from pond-reared stock - Boonyarath Pratoomchat (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 1991